Understanding self‐monitoring to inform a mobile intervention for binge eating and weight management: A proof‐of‐concept randomized trial. Issue 5 (12th March 2022) - Liu, Jianyi; Munson, Sean A.; Chang, Angela; Voss, Claire; Graham, Andrea K.
Abstract: Objective: This study explored consumers' perspectives on self‐monitoring, a common feature in behavioral interventions that helps inform consumers' progress and answer their questions, to learn what outcome metrics matter to consumers and whether self‐selection of these metrics leads to greater engagement (i.e., compliance, satisfaction) in self‐monitoring than monitoring only default options. Methods: In a proof‐of‐concept randomized trial, 48 adult participants were randomly assigned to "clinician‐determined monitoring" or "clinician + self‐determined monitoring" conditions. Before starting monitoring, all participants shared outcomes that would matter to them in a mobile intervention for binge eating and weight management. Then, for 3 weeks, participants in the "clinician‐determined" condition monitored their weight and binge‐eating episodes, and participants in the "clinician + self‐determined" condition monitored these and another metric of their choosing. After, satisfaction and compliance were assessed. Results: Participants identified 116 metrics, grouped into 12 themes, that mattered to them. During monitoring, participants in the "clinician + self‐determined" condition monitored 41 metrics. Surprisingly, participants in the "clinician‐determined" condition also monitored metrics besides weight and binge eating. This resulted in a failure of our experimental manipulation, which represents a significant limitation of this research. No significant differences emerged in satisfaction or compliance between conditions. Discussion: Although our proof‐of‐concept trial yielded null quantitative results, findings also suggested binge eating and weight management interventions may benefit from including an individually customizable monitoring option in addition to default metrics, warranting testing in future research. Public Significance: Examining consumers' self‐monitoring preferences for a mobile intervention for binge eating and weight management revealed a variety of metrics that matter to consumers, although binge eating and weight were still most valued. Findings from our proof‐of‐concept trial suggest design implications of encouraging an individually customizable monitoring option, in addition to default metrics, which needs to be tested in future research over a longer period and during actual mobile intervention delivery.